Food labeling : toward national uniformity - Porter, Donna Viola; Earl, Robert O. (National Academy Press, 1992)
Background of the study -- Contextual factors affecting the regulation of misbranded food -- Criteria for determining adequate implementation of the federal statute -- Comparison and analysis of federal and state food labeling requirements -- Issues raised by states, consumers, and industry.